The lord of the rings, the fellowship of the ring [videorecording (DVD)] - Jackson, Peter, 1961-; Wood, Elijah, 1981-; McKellen, Ian; Tyler, Liv; Mortensen, Viggo, 1958-; Astin, Sean; Blanchett, Cate, 1969-; Bloom, Orlando, 1977-; Lee, Christopher, 1922-2015; Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (New Line Home Entertainment, 2002)
In ancient times the Rings of Power were crafted by the Elven-smiths, and Sauron, the Dark Lord, forged the One Ring, filling it with his own power so that he could rule all others. But the One Ring was taken from him, and though he sought it throughout Middle-Earth still it remained lost to him. After many ages it fell, by chance, into the hands of the Hobbit, Bilbo Baggins. On his eleventy-first birthday, Bilbo disappeared, bequeathing to his young cousin, Frodo, the Ruling Ring, and a perilous quest: to journey across Middle-Earth, deep into the shadow of the Dark Lord and destroy the Ring by casting it into the Cracks of Doom.